The Unorthodox Presidency of Donald J. Trump - Rutledge, Paul E.; Rackaway, Chapman (University Press of Kansas, 2021)
"The election of Donald Trump as the 45th President of the United States was a disruptive political event the likes of which the country has not seen in decades. From his campaign through the four years of Trump's time in office, this presidency has been one of the most unorthodox in American history. As such, it provides an excellent opportunity to look at electoral politics, the institutions of American government, and US public policy through the lens of disruption. The Unorthodox Presidency of Donald J. Trump, edited by Paul Rutledge and Chapman Rackaway, brings together fourteen other contributors to provide a comprehensive midterm assessment of the Trump presidency organized by the heterodoxy of his electoral, governing, and policy approaches"--